Debates As One of the Most Effective form of Interactive English Language Learning for Medical Students - Israilova , Ilona (International Journal of Psychosocial Rehabilitation, 2020)
The article deals with peculiar type of interactive learning in the form of debates. The theoretical justification of this approach in the context of solving some specific educational objectives is observed. The potential of communicative approach in teaching medical universitystudents an English language is explored.